Table of contents and introductory materials for Vol. 43, no. 3, summer 2016 - Haijun Kang; Donna Augustine-Shaw (Educational Considerations, 2016)
This content includes the front cover, the table of contents, editorial information and more, the special issue: "Preparing and Developing Educational Leaders in International Contexts: From Policy and Theory to Preparation and Practice"